2010
DOI: 10.1002/jgm.1433
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of coxsackie and adenovirus receptor expression for gene transfer to normal and dystrophic skeletal muscle

Abstract: We have developed a method of increasing CAR levels in both normal and regenerating muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It has also been established that the abundance of myoblasts and myotubes as well as the relative abundance of CARs found in young mice contributes to greater transduction efficiency 42 53 54 . Further, the overexpression of CARs in muscle from adult transgenic mice has been shown to produce a significant increase in the transduction of skeletal muscle 55 56 . Taken together, these findings support the view that the reduced numbers of transduced motor neurons in adult mice is more than likely a consequence of the down-regulation of CARs observed throughout age.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been established that the abundance of myoblasts and myotubes as well as the relative abundance of CARs found in young mice contributes to greater transduction efficiency 42 53 54 . Further, the overexpression of CARs in muscle from adult transgenic mice has been shown to produce a significant increase in the transduction of skeletal muscle 55 56 . Taken together, these findings support the view that the reduced numbers of transduced motor neurons in adult mice is more than likely a consequence of the down-regulation of CARs observed throughout age.…”
Section: Discussionmentioning
confidence: 99%
“…As may be expected, these techniques focus on enhancing virus uptake rather than other processes essential to transduction. For instance, a complementary viral strategy can be used to boost the expression of the virus receptor(s) at peripheral nerve terminals that can then be therapeutically targeted with a different virus, as has been demonstrated with AAV-mediated CAR expression for increased AdV binding and uptake (Larochelle et al, 2010 ; Li et al, 2018b ). Receptor expression may also be selectively increased by genetic overexpression (Nalbantoglu et al, 2001 ) or administration of drugs that enhance transcription, albeit non-specifically (e.g., histone deacetylase inhibitors; Larochelle et al, 2010 ).…”
Section: Optimizing Intramuscular Gene Therapymentioning
confidence: 99%
“…For instance, a complementary viral strategy can be used to boost the expression of the virus receptor(s) at peripheral nerve terminals that can then be therapeutically targeted with a different virus, as has been demonstrated with AAV-mediated CAR expression for increased AdV binding and uptake (Larochelle et al, 2010 ; Li et al, 2018b ). Receptor expression may also be selectively increased by genetic overexpression (Nalbantoglu et al, 2001 ) or administration of drugs that enhance transcription, albeit non-specifically (e.g., histone deacetylase inhibitors; Larochelle et al, 2010 ). Similarly, genetic screens are beginning to identify a variety of viral restriction factors (i.e., proteins that constrain uptake and transduction), which could also be genetically or chemically manipulated, perhaps in a tissue-specific fashion, to aid uptake (Mano et al, 2015 ; Madigan et al, 2019 ).…”
Section: Optimizing Intramuscular Gene Therapymentioning
confidence: 99%
“…In any case, high levels of dystrophin expression seem to be required to reverse, at least partially, DMD pathology. Interestingly, Larochelle and collaborators injected AAV2 encoding CAR in adult mdx mice skeletal fibers and demonstrated that a moderate increase of CAR expression resulted in a significative increase of expression from Ad in skeletal muscle fibers [77], which could improve Ad-mediated DMD therapy and have a strong potential for non-regenerative skeletal muscle diseases.…”
Section: Gene Therapy To the Musclementioning
confidence: 99%